Case Report: Membranoproliferative Glomerulonephritis, a Rare Clinical Manifestation of Abernethy Malformation Type II - Xue He; Yueling Zhu; Haidong Fu; Chunyue Feng; Zhixia Liu; Weizhong Gu; Yanyan Jin; Binbin Yang; Huijun Shen (Frontiers Media S.A., 2021)
This report describes an 8-year-old male who presented with clinical manifestations including systemic edema, heavy proteinuria, hypoproteinemia, and persistent hypocomplementemia. Arachnoid cysts and focal nodular hyperplasia were also detected. Imaging examination and renal biopsy were performed, and Abernethy malformation type II with immune complex-mediated membranoproliferative glomerulonephritis was considered the diagnosis. Due to the persistence of embryonic vessels, Abernethy malformation is a rare congenital vascular malformation of the splanchnic venous system, which can be classified as type I (end-to-side shunt) and type II (side-to-side shunt). Abernethy malformation with glomerulonephritis remains extremely rare. In the patient described, glomerulonephritis mediated by immune complex with "full-house" positive immunohistochemistry was confirmed on renal biopsy. In addition, he was treated with glucocorticoids and tacrolimus. Whether surgical treatment is necessary should be determined according to the state of the disease in the later stages. The present case reflects the association between the congenital portosystemic shunt and the renal region and, to the authors' knowledge, may be the first report to describe arachnoid cysts as a symptom of Abernethy malformation.